Signaling effects of monetary policy - Leonardo Melosi (Federal Reserve Bank of Chicago, 2016)
We develop a dynamic general equilibrium model in which the policy rate signals the central bank's view about macroeconomic developments to price setters. The model is estimated with likelihood methods on a U.S. data set that includes the Survey of Professional Forecasters as a measure of price setters' inflation expectations. This model improves upon existing perfect information models in explaining why, in the data, inflation expectations respond with delays to monetary impulses and remain disanchored for years. In the 1970s, U.S. monetary policy is found to signal persistent inflationary shocks, explaining why inflation and inflation expectations were so persistently heightened. The signaling effects of monetary policy also explain why inflation expectations adjusted more sluggishly than inflation after the robust monetary tightening of the 1980s.
Keywords: E52; C11; C52; D83; 330; disanchoring of inflation expectations; heterogeneous beliefs; endogenous signals; Bayesian VAR; Bayesian counterfactual analysis; Delphic effects of monetary policy